Enhancing mental flexibility: The effect of a training program based on the concept of physical self and psychological adaptation among secondary school students in Al-Ahsa - Aldawsari, Hussam K. (International Journal of Innovative Research and Scientific Studies, 2025)
The research focused on developing structured methods to improve mental toughness as a critical tool for addressing academic challenges and promoting psychological adaptation. This study aimed to investigate the effectiveness of a mental toughness training program in enhancing physical self-understanding and psychological adjustment among university students at the College of Education, King Faisal University, Saudi Arabia. The study employed an experimental approach. The final sample consisted of 56 students, divided equally into experimental and control groups. Data collection relied on standardized questionnaires designed to assess mental toughness, physical self-concept, and psychological adjustment. The results revealed significant improvements in the experimental group compared to the control group across all measured variables. The findings underscore the importance of integrating mental toughness training programs into educational settings to foster holistic development among university students. Such programs enhance both psychological resilience and physical self-awareness, equipping students to better manage stress, improve academic performance, and achieve long-term personal growth. Future research should explore the sustainability of these effects and expand the scope to include diverse populations and contexts. This study provides valuable evidence supporting the role of mental toughness as a foundational skill for modern education and serves as a basis for designing similar interventions tailored to specific needs. By combining structured training with innovative approaches, universities can create supportive environments that promote resilience, confidence, and adaptability among students.